Taxonomy and Characterization of Bioactive Metabolites from a New Marine Microorganism Strain MLA-21 - Xing, Yingying; Ma, Yihua; Lu, Yuanyuan; Xi, Tao (Asian Journal of Chemistry, 2012)
Marine actinomyces MLA-21 was isolated from Arctic sediment samples. The strain was identified by the methods of morphology, physiological and chemotaxonomic characterization and 16S rRNA gene sequence analysis. The results showed that the strain was a new marine variable species of S. coelicolour. Two active compounds were isolated and purified from the fermentation of the strain and their antitumor activity against HepG-2, MCF-7 and A549 cell lines were defined by vitro cytotoxic activity assay. Their structures were elucidated as methyl p-hydroxybenzoate (1) and 3-(4-propylphenoxy)-propanoic acid (2) by 1H and 13C NMR and EI-MS spectroscopic methods. Compounds 1 and 2 were isolated from marine microorganism for the first time.